Understanding the perceived quality of professors' teaching effectiveness in various disciplines: the moderating effects of teaching at top colleges. Issue 3 (3rd April 2019) - Chiu, Ya-Ling; Chen, Ku-Hsieh; Hsu, Yuan-Teng; Wang, Jying-Nan
Abstract: Measuring the perceived quality of professors' teaching effectiveness is a critical issue in higher education. This study involves a large-scale data exploration with a sample of 16, 802 professors, in which each professor had received at least 20 ratings from the RateMyProfessors website. We find that perceived difficulty (from the students' perspective) has a significantly negative effect on perceived quality. However, when professors teach more difficult courses at top colleges, the decline in perceived quality is relatively small when compared to other colleges. In other words, whether professors come from top colleges has a moderating effect on the relationship between perceived quality and perceived difficulty. Furthermore, through a consideration of the characteristic differences among disciplines in terms of the relationship between perceived quality and perceived difficulty, we obtain three specific groups of disciplines. These findings facilitate a better understanding of quality for professors from different disciplines. We suggest that the measurement of teaching effectiveness should avoid the use of a single criterion because differences in courses, disciplines or schools can influence the measurement results, and these factors are beyond the control of professors.